2005
DOI: 10.1152/ajpheart.00856.2004
|View full text |Cite
|
Sign up to set email alerts
|

Fibrinogen and fragment D-induced vascular constriction

Abstract: Elevated fibrinogen (Fg) concentration in blood is a high risk factor for many cardiovascular diseases. We hypothesize that Fg and its early degradation product, fragment D, may result in arterial constriction by binding endothelial intercellular adhesion molecule-1 (ICAM-1). The vasoconstriction induced by Fg and fragment D was studied in third-and second-order arterioles (3As and 2As, respectively) of Sprague-Dawley rat cremaster muscle in vivo, in aortic and femoral artery rings, and in the segments of firs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
65
1
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 35 publications
(69 citation statements)
references
References 41 publications
2
65
1
1
Order By: Relevance
“…We also measured fluorescence intensity in target venules and found it to be decreased after infusion of Fg. This can be explained by decreased arteriolar diameters in response to an increased blood content of Fg (Lominadze et al, 2005(Lominadze et al, , 2010 and leakage of FITC-BSA from a vessel to interstitium. Combined with the fluorescence intensity increase in interstitium, these data suggest even a greater effect of Fg in disruption of BBB.…”
Section: Limitations Of the Studymentioning
confidence: 99%
See 1 more Smart Citation
“…We also measured fluorescence intensity in target venules and found it to be decreased after infusion of Fg. This can be explained by decreased arteriolar diameters in response to an increased blood content of Fg (Lominadze et al, 2005(Lominadze et al, , 2010 and leakage of FITC-BSA from a vessel to interstitium. Combined with the fluorescence intensity increase in interstitium, these data suggest even a greater effect of Fg in disruption of BBB.…”
Section: Limitations Of the Studymentioning
confidence: 99%
“…We showed that high content of undegraded Fg can cause an arteriolar constriction (Lominadze et al, 2005) and disruption of endothelial cell (EC) layer integrity Tyagi et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…We recently showed that Fg binding to ICAM-1 causes constriction of arterioles in vitro and in vivo [28]. In isolated perfused microvessels, a higher than normal concentration of intact Fg (~2 mg/ml), in addition to binding to ECs, binds to vascular smooth muscle cells [28].…”
Section: Introductionmentioning
confidence: 99%
“…Next, we examined whether ICAM-1 promotes EGFR-dependent mucin production via binding to fibrinogen. We examined fibrinogen for the following reasons: first, fibrinogen has been shown to bind to the first extracellular domain of ICAM-1 (15); second, the binding of fibrinogen to ICAM-1 has been shown to induce cell signaling (22,34,47); and third, fibrinogen has been found on the airway mucosal surface in rodent models of allergic airway inflammation (18,67) and in the airways of subjects with acute severe asthma (67), COPD (45), and cystic fibrosis (64). In airways, fibrinogen has been shown to inactivate surfactant (53) and to induce airway hyperresponsiveness (67); a potential role for ICAM-1 in these fibrinogen effects was not examined in those studies.…”
Section: Discussionmentioning
confidence: 99%
“…Fibrinogen is present in mucous plugs, is increased in the airways of subjects with acute severe asthma (67), COPD (45), and cystic fibrosis (64), and has been shown to induce ICAM-1-dependent signaling in endothelial (34,47) and immune (22) cells. The effects of fibrinogen binding to ICAM-1 on airway epithelial cells are unknown.…”
mentioning
confidence: 99%